Outcomes of patients with COVID-19 Acute Respiratory Distress Syndrome requiring Invasive Mechanical Ventilation admitted to an Intensive Care Unit in South Africa - Arnold-Day, Christel (Department of Anaesthesia and Perioperative Medicine, 2023)
Background Up to 30% of patients with COVID-19 pneumonia may require ICU admission or mechanical ventilation [Guan et al., 2020; Huang et al., 2020]. Data from low- and middle-income countries for COVID-19 ARDS are limited. Groote Schuur Hospital in Cape Town, South Africa expanded its ICU service to support patients with COVID-19 ARDS requiring invasive mechanical ventilation (IMV). We report on patients' characteristics and outcomes from two pandemic waves. Methods All patients with COVID-19 ARDS admitted to the ICU for IMV were included in this prospective cohort study. Data were collected from 5th April 2020 to 5th April 2021. Ethical approval was granted (HREC: 362/2020), consent was waived for deceased patients and deferred for survivors. Results Over the 12-month study period 461 patients were admitted to the designated COVID-19 ICU. Of these, 380 patients met study criteria and 377 had confirmed hospital discharge outcomes. The median age of patients was 51 years (range 17-71), 50.5% were female and the median BMI was 32kg/m2 (IQR 28-38). The median P/F ratio was 97 (IQR 71.5-127.5) after IMV was initiated. Comorbidities included diabetes (47.6%), hypertension (46.3%) and HIV infection (10%). Of the patients admitted, 30.8% survived to hospital discharge with a median ICU length of stay of 19.5 days (IQR 9- 36). Predictors of mortality after adjusting for confounders were: male (OR:1.79), increasing age (OR:1.04) and SOFA score (OR:1.29). Conclusion In a resource limited environment, escalation of ICU IMV support achieved a 30.8% hospital survival in patients with COVID-19 ARDS. The ability to predict survival remains difficult given this complex disease.